Physical activity levels of Portuguese adolescents in the first period of confinement due to the COVID19 pandemic and the first activities of teachers and coaches: A cross-sectional study - Gomes, L.; Martins, J.; Ramos, M.; Costa, F. C. Da (Retos, 2023)
Due to the COVID-19 pandemic, social confinement was declared in Portugal on 19th March 2020. Schools and sports clubs were closed, access to all sports and leisure facilities was limited, and young people have experienced restrictions regarding the practice of physical activities and sports. The purpose of this study was to identify the physical activity (PA) levels and sports participation of adolescents before and during confinement, with whom they practice during restrictions and to identify the activities adopted by their physical education (PE) teachers and sports coaches to keep them physically active. An online survey was conducted between March 27th and April 14th 2020. A total of 3,012 Portuguese adolescents (57% females) aged between 10 and 19 years old (14.3±2.4 years old) took part in this study. Wilcoxon test and paired-sample t-test and chi-square test of independence were used in the data analysis. The results show that the number of students engaged in PA increased during the lockdown (72.7% to 88.2%). For those who practiced PA before lockdown, the frequency of PA decreased from 4.7 sessions/week to 4.4 sessions/week (during confinement). For those who did not practice PA before confinement, they started by doing 4.1 sessions/week. The vast majority of PE teachers (77.3%) proposed some pedagogical activities such as video conference classes (53.6%). Regarding the coaches, 53.4% proposed some activity, mainly time circuit training, walking and cycling (around 18% each), or specific training exercises and video conference classes (about 12% each). The number of students who increased their regular PA practice can be justified by the immediate intervention of PE teachers, who implemented several online activities, or because students were able to choose different options to stay active.